Sentencias de alimentos y su relación con la satisfacción del cumplimiento de pago a menores, Iquitos 2022 - Cabanillas Tuiro, Beula Berenice (2025)
In this research titled “Maintenance Sentences and Their Relationship with Satisfaction in Payment Compliance to Minors, Iquitos 2022”, the general objective was to determine the relationship between maintenance sentences issued by the Judiciary and the level of satisfaction with payment compliance to minor beneficiaries within the jurisdiction of Iquitos during the year 2022. The study sample included 103 maintenance claimants representing minors from the districts of Punchana, Belén, San Juan, and Iquitos. The study, with a legal and quantitative approach, used a non-experimental cross-sectional design, allowing the level of compliance with the maintenance obligations established by court order and its impact on the satisfaction of the demanding users to be identified. As main results, a low percentage of compliance with a 13.6% was evident in compliance with alimony, while satisfaction regarding compliance with sentences was only 12.6%. Likewise, it was found that 86,4% of the users interviewed stated that payment compliance does not cover the basic needs of the minor, such as education, health, clothing and recreation. Regarding the statistically significant relationship between the study variables that are the food sentence and user satisfaction, a P value = 0.000 was found; which means that both variables are dependent. The findings of this research reveal not only the deficient level of compliance within the context of maintenance law but also a shortfall in the execution of judicial resolutions, underscoring the need for effective measures to enhance the efficiency of judicial processes in this area.